Marcadores discursivos y relato conversacional - Berenguer, Josefa A. (Caplletra. Revista Internacional de Filologia, 1995)
This is a part of a broader research about discourse markers in consversational storytelling, and has been carried out by the author on a bilingual (Catalan/Spanish) corpus. The paper focuses on markers such as resulta que, lo que passa és que and el cas és que, whose function consists of the introduction of new discourse topics.